Outcome of relapse after allogeneic stem cell transplant in patients with acute myeloid leukemia. Issue 6 (1st June 2013) - Devillier, Raynier; Crocchiolo, Roberto; Etienne, Anne; Prebet, Thomas; Charbonnier, Aude; Fürst, Sabine; El-Cheikh, Jean; D'Incan, Evelyne; Rey, Jérôme; Faucher, Catherine; Blaise, Didier; Vey, Norbert
Abstract: Although allogeneic stem cell transplant (Allo-SCT) is an effective treatment for high-risk acute myeloid leukemia (AML), relapses remain a major cause of treatment failure. There is currently no standard of care for post-transplant relapse of AML, but the increasing numbers of investigational agents in this setting require a better knowledge of their outcome. We retrospectively evaluated the efficacy of salvage therapies in 54 patients with AML relapsing after Allo-SCT. Twenty-four patients received intensive salvage treatment (17 non-intensive chemotherapy, 13 supportive care). Complete remissions (CRs) were seen only in the group who received intensive salvage (CR rate: 17/24 [71%]). One-year overall survival was 19% (median: 3.4 months) in the whole study group and 33% in the intensive savage group (vs. 7% for patients without intensive salvage, p = 0.004). Factors influencing overall survival (OS) were: time to relapse after Allo-SCT (hazard ratio [HR]: 3.7 [1.6–8.8]) and performance status (PS) at relapse (HR: 2.2 [1.1–4.4]) by multivariate analysis. Our results confirm the poor prognosis of AML relapse after Allo-SCT. In selected patients salvage chemotherapy produces CRs, but these are short lived. Other strategies aiming at modulating immune antileukemic activity have to be developed.